RANCANGAN KEMASAN PELINDUNG BUAH APEL SELAMA TRANPORTASI BERBAHAN DASAR ECENG GONDOK DAN SABUT KELAPA - Ida Ayu Widhiantari; Amuddin Amuddin; Rosyid Ridho; Fakhrul Irfan Khalil; Isnaini Puspitasari (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Packaging during the transportation process greatly influences the damage to horticultural products. Harvest apples are usually packed in wooden boxes or bamboo baskets and stacked until they reach maximum capacity. This makes the fruit easily damaged by bruising due to high piles. Based on these conditions, it is necessary to handle horticultural products in the form of apples to reduce damage to the fruit during transportation to maintain the quality of the apples until they reach consumers and extend the shelf life of the fruit. This research aims to design protective packaging for apples from a combination of water hyacinth and coconut fiber. The experimental method was carried out in this research with 2 factors consisting of 3 levels; factor one the combination of packaging materials, and factor two was the pressure of the packaging printer. Nine experimental units were obtained from the combination of the two treatments, namely K1T1 (E 90% + S 10%) with a pressing pressure of 400 psi, K1T1 (E 90% + S 10%) with a pressing pressure of 700 psi, K1T1 (E 90% + S 10% ) with a pressing pressure of 1000 psi, K2T1 (E 60% + S 40%) with a pressing pressure of 400 psi, K2T2 (E 60% + S 40%) with a pressing pressure of 700 psi, K2T3 (E 60% + S 40%) with pressing pressure 1000 psi, K3T1 (E 30% + S 70%) with pressing pressure 400 psi, K3T2 (E 30% + S 70%) with pressing pressure 700 psi, K3T3 (E 30% + S 70%) with pressing pressure 1000 psi. The results showed that the combination treatment of K2T2 with a pressing pressure of 700 psi provided the best protective quality for apples with the lowest percentage of mechanical damage and reduction in apple mass, at 5.556%, 2.55%, respectively. The springiness and texture values for apples were the highest with values respectively 3.17 mm, 16.7335N. Meanwhile, the highest packaging compressive strength value was obtained in the K3T3 treatment with a value of 26.164N.